PENGARUH MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALLY, REPETITION) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Olisa Tania; Safrihady; Dewi Mariana (STKIP Subang, 2026)
This study aims to determine the effect and the magnitude of the effect of the AIR (Auditory, Intellectually, Repetition) learning model on the reading comprehension ability of fifth-grade students at SDS Torsina II Singkawang. This research employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest design. The sample consisted of 30 students. Data collection techniques used in this study were measurement and test instruments. The data analysis techniques included descriptive statistical analysis, Shapiro-Wilk normality test, hypothesis testing using the nonparametric Wilcoxon Signed Rank Test, and effect size calculation. The results of descriptive analysis showed that the mean score of the pretest was 2.19 with a standard deviation of 0.840, while the mean score of the posttest was 3.19 with a standard deviation of 0.66, indicating an improvement in students’ reading comprehension ability. The normality test results indicated that the data were not normally distributed (Sig < 0.05), thus the analysis was continued using the Wilcoxon test. The results of the Wilcoxon test showed that all significance values were less than 0.05, indicating a significant difference between pretest and posttest scores. Furthermore, the effect size calculation resulted in a value of 0.841, which is categorized as a large effect. In conclusion, the AIR (Auditory, Intellectually, Repetition) learning model has a significant and strong effect on the reading comprehension ability of fifth-grade students at SDS Torsina II Singkawang.